Composition of the Essential Oils of Two Umbelliferae Herbs (Artedia squamata and Malabaila secacul) Growing Wild in Turkey - Bagci, Eyup; Dogan, Gulden (Taylor & Francis Ltd, 2015)
Apiaceae are a family of medicinal plants widely used in traditional medicine and they are employed commercially as species or drugs because of their richness on useful secondary metabolites. The Artedia L. genus is a monotypic genus in Flora of Turkey and it is represented with a single species Artedia squamata L. Malabaila secacul Banks & Sol. is reported as very variable species in Flora of Turkey and it is represented as different groups taxonomically. In this study, water-distilled essential oils from the aerial parts of Artedia squamata and Malabaila secacul were analyzed by GC and GC-MS system. Fifty three components representing 99.7 % of the oil of A. squamata were identified of which alpha-pinene (57.8 %), camphene (9.0 %), beta-myrcene (5.7 %), delta-3-carene (5.3 %) and limonene (5.3 %) were found to be the major constituents. Butanoic acid (37.1 %), caryophyllene oxide (13.4 %), germacrene D (10.0 %) and beta-caryophyllene (5.4 %) were the main compounds identified in the oils of M. Secacul, representing 90.2 % total oil.
Keywords: Essential oil; GC-MS; alpha-pinene; Malabaila secacul; germacrene D; Artedia squamata; Umbelliferae